HOME ECONOMICS EXTENSION FOR MARKET WOMEN IN SOUTH-WESTERN NIGERIA: THE CASE FOR ILE-IFE - LADIPO , P.; ROBERTS, P. (The Faculty of Agriculture Obafemi Awolowo University, Ile-Ife, Nigeria., 2020)
This study was designed to gain information which could guide the development of home economics extension programmes for market women in south-western Nigeria. The objectives were to: (1) determine the need for and define the scope of home economics programmes; and (2) explore the feasibility of introducing programmes through women's marketing associations. The methods used were interviewing 207 market women and the officers of 17 associations and experimentally conducting a short programme with one association. The findings suggest that any programme must deal with both women's economic and domestic roles within the reality of the market place and that stable associations could function as participating units in home economics programmes.